Motivasi dan Perilaku Penggunaan Media Sosial Generasi Z dalam Melakukan Perjalanan Wisata - Helga Liliani (Universitas Multimedia Nusantara, 2018)
The number of Generation Z in Indonesia has reached 68 million people and equals to 47.5% of the number of internet users in Indonesia. They are considered as a potential consumer group for various business industries, including tourism. The survey conducted by Tirto.id shows that Generation Z has an important influence in forming vacation decisions, both for themselves and their families. Therefore, it is important for tourism industry players to be able to find out their motivation in traveling. In addition, Generation Z who has been connected to the internet also use social media to find information about tourist destinations. Therefore, their behavior in utilizing social media must be well identified. This research is quantitative-descriptive, using a purposive-incidental survey method to collect research data. The results showed that respondents had external motivation in the form of attributes possessed by the destination region, and Instagram and Kaskus were social media that had a significant influence in the process of forming vacation decisions. Keywords: Generation Z, travelling motivation, travelling behavior, travel activity